Multicultural education in the context of perception of educational texts - ROMANOV, I.V (Journal of Education, Technology and Computer Science, 2016)
Globalization of social relations determines the range and vector of development of main operative forces of communicative interaction. In particular, innovative technologies and multiculturalism of the information flows become defining, which is especially important in the issues of modern education. There is a significant strengthening of the role of the multicultural component of information represented in a sign form and creating a materialized mediator in the interaction of consciousnesses. The article deals with the questions of a multicultural aspect of educational information in the learning process.